2019
DOI: 10.1590/1414-431x20187905
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexmedetomidine against organ dysfunction in a two-hit model of hemorrhage/resuscitation and endotoxemia in rats

Abstract: Dexmedetomidine (DEX), a selective agonist of α 2 -adrenergic receptors, has anti-inflammation properties and potential beneficial effects against trauma, shock, or infection. Therefore, this study aimed to investigate whether DEX might protect against multiple-organ dysfunction in a two-hit model of hemorrhage/resuscitation (HS) and subsequent endotoxemia. Eighty Wistar rats were randomized into four groups: NS (normal saline), HS/L (HS plus lipopolysaccharide), HS/L+D (HS/L plus dexmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Natural antioxidants have shown a beneficial effect on the cellular apoptosis and thus antioxidants are explored as an AD treatment. The literature has suggested that dexmedetomidine has strong antioxidant and anti-inflammatory properties [10]. Data of the present investigation suggest that cepharanthine alone and in combination with dexmedetomidine ameliorates the altered level of oxidative stress and production of ROS and MMP in SD rats.…”
Section: Discussionsupporting
confidence: 51%
“…Natural antioxidants have shown a beneficial effect on the cellular apoptosis and thus antioxidants are explored as an AD treatment. The literature has suggested that dexmedetomidine has strong antioxidant and anti-inflammatory properties [10]. Data of the present investigation suggest that cepharanthine alone and in combination with dexmedetomidine ameliorates the altered level of oxidative stress and production of ROS and MMP in SD rats.…”
Section: Discussionsupporting
confidence: 51%
“…Dexmedetomidine (Dex), a highly selective α 2 -adrenegicreceptor (α 2 AR) agonist, can reduce pulmonary edema through inhibiting the production of inflammatory cytokines, including TNF-α, IL-1β and IL-6 in ALI model [13][14][15][16]. Consistent with these studies, our previous studies have found that Dex can attanuate pulmonary edema in LPSinduced ALI, and improve the PaO 2 , reduce the inflammatory response.…”
Section: Introductionmentioning
confidence: 59%
“…a number of basic research experiments and clinical trials have reported that dex can protect various organs, including the lungs, by inhibiting oxidative stress, inflammatory responses and apoptosis in a range of diseases (18)(19)(20). The protective effects of dex were recently demonstrated in a two-hit rat model (21). a recent study has shown that dex is relevant to the inhibition of NLRP3 inflammasome activity (19).…”
Section: Introductionmentioning
confidence: 99%